EGG ROLL TAPE KETAN HITAM BUAH NAGA SEBAGAI ALTERNATIF MAKANAN SELINGAN TINGGI SERAT DAN ANTIOKSIDAN - Ladytanesia Ervita Bela Sukowati; Roro Nur Fauziyah; Yenny Moviana; Agustina Indri Hapsari; Gurid Pramintarto Eko Mulyo (Jurnal Gizi dan Dietetik, 2023)
Egg Roll based on fermented glutinous black rice and dragon fruit is a snack product high in fiber and antioxidants. The purpose of this study is to determine the three best formulations and to determine the effect of different balances on the preferences levels, fiber content, anthocyanin, and antioxidant activity.  The design of this study is an experimental with Completely Randomized Design (CRD). The research method uses hedonic test for preference level, enzymatic gravimetry for fiber, differential spectrophotometry for anthocyanins, and Uv-Vis DPPH spectrophotometry for antioxidant activity. This study involved 30 moderately trained panelists who were students of the Department of Nutrition, Poltekkes, Ministry of Health, Bandung. The data were analyzed using the Kruskal Wallis Test and continoud with the Man Whitney Test. The results of the hedonic test show that formula 1 with a balance of 30% fermented glutinous black rice: 70% dragon fruit has the highest level of preference in aspects of color, taste, aroma, texture, and overall. The results of the Kruskal Wallis test show that there are differences in aspects of color, taste, aroma, texture, and overall. The highest fiber is found in formula 3 which is 6.31 g/100g. The highest anthocyanin is found in formula 3 which is 22.64 mg/100g. The antioxidant activity of IC 50 is 186.15 ppm. This product can be developed as a snack source of fiber and antioxidants.